2012
DOI: 10.3724/sp.j.1263.2012.03051
|View full text |Cite
|
Sign up to set email alerts
|

Association of glomerular filtration rate with arterial stiffness in Chinese women with normal to mildly impaired renal function

Abstract: ObjectiveBoth decreased glomerular filtration rate (GFR) and arterial stiffness were considered as risk factors for atherosclerosis. Previous studies have suggested the association between central arterial stiffness and the degree of GFR loss. Whether decreased GFR contributes to peripheral artery stiffness remains controversial. Moreover, data analyzed from a cohort of Chinese women are rare. Our aim was to explore the relationship between GFR and regional arterial stiffness in Chinese women.MethodsIn this cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…Our results indicate that arterial stiffening is independently associated with minimally reduced eGFR and MAU. These results agree with previous studies of high risk patients with moderate or severe renal dysfunction patients 8-10). However, our results are important because patients with more than moderate renal dysfunction as assessed by eGFR values of <60 mL/min/1.73 m 2 were excluded and we assessed the independent impact of MAU and eGFR on arterial stiffness.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results indicate that arterial stiffening is independently associated with minimally reduced eGFR and MAU. These results agree with previous studies of high risk patients with moderate or severe renal dysfunction patients 8-10). However, our results are important because patients with more than moderate renal dysfunction as assessed by eGFR values of <60 mL/min/1.73 m 2 were excluded and we assessed the independent impact of MAU and eGFR on arterial stiffness.…”
Section: Discussionsupporting
confidence: 92%
“…Bian's study showed that carotid-femoral PWV and Augmentation index increased on going from the top to the bottom eGFR tertile in Chinese women with normal kidney function 8). Astor et al11) also noted that both lower eGFR and MAU increased CV mortality, but they compared moderately decreased eGFR (eGFR <60 mL/1.73 m 2 ) with normal eGFR (>90 mL/1.73 m 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As renal perfusion and subsequent kidney function may also be affected by abnormal blood flow patterns, in chronic kidney disease (CKD), non-invasive markers such as aortic stiffness have also been used as predictive and prognostic markers of renal function [ 10 , 11 ]. There is limited evidence to link aortic stiffness with renal function in non-kidney disease patients [ 12 - 14 ], and its role after cardiac surgery is yet to be investigated. However, preliminary data does suggest that elevated arterial stiffness may be an early predictor of renal function decline in the general population [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that cfPWV increases as GFR falls [ 29 ]. Decreased GFR exhibited a significant reverse association with cfPWV in women with normal to mildly impaired renal function [ 30 ]. Coronary artery disease patients with impaired renal function had greater cfPWV compared to those with coronary artery disease patients and normal renal function [ 31 ].…”
Section: Discussionmentioning
confidence: 99%